Legal Certainty of Court Clerks’ Obligation to Notify Guardianship Appointments to the Balai Harta Peninggalan in Indonesia - Zulfa Zahara Imtiyaz; Rachmi Sulistyarini; Amelia Sri Kusuma Dewi (RADJA PUBLIKA, 2026)
This article examines the legal certainty of the obligation of court clerks to notify guardianship appointments to the Balai Harta Peninggalan (BHP) within the Indonesian legal system. Although the Indonesian Civil Code establishes the normative basis for notification and recognizes the BHP as a supervisory guardian, the procedural framework governing the implementation of this obligation remains insufficiently detailed, particularly with regard to notification procedures, timing, and uniform application across courts. This study employs normative legal research using statutory, conceptual, and case approaches. Primary and secondary legal materials are analyzed to examine the regulatory framework governing guardianship, the role of the BHP, and selected court determinations. The analysis reveals a regulatory gap between the existence of the normative obligation and the absence of comprehensive procedural mechanisms for its implementation. The gap is particularly evident in the different approaches adopted by General Courts and Religious Courts, resulting in variations in institutional supervision and the protection of children’s property. This study contributes a normative reconstruction by proposing a standardized notification mechanism and a maximum seven-day period for court clerks to notify the BHP. Such regulation is necessary to strengthen legal certainty, institutional accountability, and the protection of children’s rights in guardianship proceedings.